Awareness of oral cancer, oral premalignant disorders and their risk factors among adult population in Bareilly city - Shivani Singh; Abhijeet Alok; L Nagesh; K K Shivalingesh; Vikash Kumar Sah; Indra Deo Singh (Wolters Kluwer Medknow Publications, 2020)
Background: Oral cancer and oral premalignant disorders (OPMDs) are serious problems worldwide. Awareness regarding the signs, symptoms, and risk factors of oral cancer is very less in India, especially in people with low socioeconomic status. Aim and Objectives: The aim of this study was to assess the awareness of oral cancer, OPMD and their risk factors among the adult population in Bareilly City and the objective was to investigate the level of public awareness regarding the risk factors associated with oral cancer and OPMD among a selected sample of the adult population in Bareilly City. Materials and Methods: The present study was a house-to-house survey in Bareilly City, Uttar Pradesh (India). A self-administered questionnaire was used to collect data from a random sample of 800 subjects from different colonies of Bareilly City. The questionnaire included 25 questions pertaining to knowledge about oral cancer, its causative factors, key symptoms, and others. Each subject was given questionnaire, and filled form was collected from each subject. Results: About 71.8% of total subjects were aware of oral cancer while 43.3% people were aware of oral potentially malignant disorders. Subjects who studied till postgraduation were more aware about oral cancer. Professionals (82.8%) were more aware about oral cancer followed by housewives. Middle-age group (75.2%) participants were also found to be more aware. Conclusion: Awareness of oral cancer and OPMD were poor in homemakers, less skilled and uneducated persons, indicating an urgent need to implement public health education and promotion strategies.